KETIMPANGAN PERLINDUNGAN ANAK DI JAKARTA : GRADIEN SOSIAL DAN 'HUKUM INTERVENSI TERBALIK' - Supriadi, Dedi; Saprizon, Saprizon; Putri, Aslina; Wirnawan, Frendli; Afandi, Ahmad; Alpian, Alpian; Fikri, KMS. Novyar Satriawan (Bhinneka Multidisiplin Journal, 2025)
Contact with child protection systems are a key site of the expression of social inequalities, yet research into the size and nature of this relationship remains sparse in Jakarta system context. This article reports on a study of the relationships between child protection system contact and small area-level deprivation. Using a national linked dataset including all children with system contact in 2013–14, (n =13,851 children) it found there is a marked relationship between deprivation and system contact, and signiﬁcant diﬀerences between regions for all three outcomes of interest. Compared to children living in the least deprived quintile of small areas, children in the most deprived quintile had, on average, 13 times the rate of substantiation, 18 times the rate of a family group conference, and 6 times their chance of placement in foster care. There was limited evidence for the ‘inverse intervention law’ that proposes that children in similarly deprived small areas have higher rates of child protection system contact if they live in less deprived regions (larger areas). The pattern of placements showed the strongest support for this law, with children in similarly deprived small areas having, on average, almost twice the rate of placement if they lived in less deprived regions compared to more deprived regions. These ﬁndings have implications for policy, as they suggest a need to apply an inequalities perspective to child protection similarly to health inequities. Speciﬁcally, action is needed to address the causes of deprivation, provide services that respond to families living in poverty, address biases, and undertake further research to examine the interactions between demand and supply of services between similar deprivation levels.